Aging Parents - National Agricultural Library (USDA), Beltsville, MD. Family Information Center (Washington, D.C.: Distributed by ERIC Clearinghouse, 1990)
This document contains a brief bibliography of peer-reviewed literature, with abstracts, on aging parents. It is one of 12 bibliographies on aging prepared by the National Agricultural Library for its "Pathfinders" series of publications. Topics covered by the other 11 bibliographies include adult children, dementia and Alzheimer's disease in the elderly (written for educators), dementia and Alzheimer's disease in the elderly (written for consumers), family caregiving, family support networks, grandparenting, humor in later life, intergenerational relationships, living arrangements in later life, pets and the elderly, and sibling relationships in adulthood. This bibliography on aging parents contains citations for 17 books and articles for researchers and educators, and 19 books and articles for consumers. It concludes with a list of organizations that readers may contact for further assistance. (NB)
ERIC Note: For other bibliographies in the series, see CG 022 490-491 and CG 022 493-500.
Researchers.
Teachers.
Community.
Practitioners.
Microfiche.
Keywords: Adult Children; Aging (Individuals); Older Adults; Parent Child Relationship; Parents; Reference Materials, Bibliographies